Childhood obesity: State of art and future research directions - Beatriz García Cortés (Revista Sobre la Infancia y la Adolescencia)
According to the World Health Organization (WHO), the childhood obesity affects 42 million children worldwide, 35 million of whom live in the developing countries (WHO, 2010).